Manichaeism in Mesopotamia and the Roman East - Lieu, Samuel N. C. (Religions in the Graeco-Roman World, 1999)
The study of Manichaeism, the first Gnostic world religion, has made major advances in the last few decades thanks to the continuing discovery and decipherment of genuine Manichaean texts from Egypt and Central Asia. This work brings together a number of major articles by the author published between 1981 and 1992 on the history of the sect in Mesopotamia and the Roman Empire. The studies have all been up-dated in the light of newly published material.